Analisis Kelayakan Finansial Pada Tanaman Lada di Kabupaten Lampung Timur - Zulkarnain - zulkarnain; Muhamad gary ranchianowarganegara (Politeknik Negeri Lampung., 2020)
The role of the agricultural sector in Indonesia is led to increasing agricultural production. One of the sub-sectors in the agricultural sector that give quite a big contribution to the national economy is the farming plant sub-sector. One of the export commodities from the farming plant sub-sector that has an important role in the economy is the pepper plant. Farming plant productivity had not been optimum and farmers paid low attention to the quality of their plants so that it will affect the price in which it will also give the influence to profit level of them that will get smaller, while, life necessity is getting bigger. The study aimed to analyze the financial expediency of pepper plants in the district of Margatiga, East Lampung regency. The location of the study was in Margatiga district, East Lampung regency. The respondents in this study were pepper farmers in Margatiga districts, East Lampung regency with the total was 56 farmers who had been chosen by simple random sampling. Financial analysis was used to answer the research question. The finding result shows that pepper farmings in the district of Margatiga in East Lampung regency were financially profitable and feasible to develop.